Menganalisis Siklus Anggaran APBN/APBD - M, Molisah; Pangestoeti, Wahjoe; Putri, Marzila; Saragih, Puja Wanti; Marvela, Jana (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study presents an analysis of the budget cycle of the State Revenue and Expenditure Budget (APBN) and Regional Revenue and Expenditure Budget (APBD) in Indonesia, with a focus on efficiency and accountability in public financial management. The research methods used include surveys, interviews and analysis of budget data from various trusted sources. The research results show that the APBN/APBD budget cycle experiences challenges in achieving optimal efficiency and accountability. First, in the planning phase, there is a need to strengthen community participation in the budget preparation process to increase accountability and transparency. Active involvement of all stakeholders is expected to increase the legitimacy of budget decisions. Second, in the implementation phase, several obstacles were found related to budget management, including the low quality of supervision and control, as well as a lack of capacity of the relevant institutions. This raises the risk of misuse and waste of the budget, threatening the efficient use of public resources. Third, in the evaluation and reporting phase, transparency and accountability are still the main problems. Lack of transparency in public financial reporting can reduce public trust in the government and make it difficult to monitor financial performance. In order to increase the efficiency and accountability of public financial management, strategic steps are recommended, including increasing public participation in the budget planning process, increasing supervision and control during implementation. budget, as well as increasing transparency and accountability through financial reporting that is more open and easy to understand. These steps are expected to optimize the use of public resources and improve government financial performance at the national and regional levels.